2020
DOI: 10.3390/ijms22010020
|View full text |Cite
|
Sign up to set email alerts
|

The Delta-Specific Opioid Glycopeptide BBI-11008: CNS Penetration and Behavioral Analysis in a Preclinical Model of Levodopa-Induced Dyskinesia

Abstract: In previous work we evaluated an opioid glycopeptide with mixed μ/δ-opioid receptor agonism that was a congener of leu-enkephalin, MMP-2200. The glycopeptide analogue showed penetration of the blood–brain barrier (BBB) after systemic administration to rats, as well as profound central effects in models of Parkinson’s disease (PD) and levodopa (L-DOPA)-induced dyskinesia (LID). In the present study, we tested the glycopeptide BBI-11008 with selective δ-opioid receptor agonism, an analogue of deltorphin, a pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…After the end of reperfusion, in a subgroup of hearts, atria were removed, and the total ventricles were used to determine the infarcted area as described previously [ 34 , 35 ]. Briefly, frozen ventricles were cut to 7–8 equal slices and placed into triphenyl-tetrazolium chloride solution (Sigma-Aldrich, Saint Louis, MO, USA) for 10 min at 37 °C followed by a 10 min formaldehyde fixation and phosphate buffer washing steps.…”
Section: Methodsmentioning
confidence: 99%
“…After the end of reperfusion, in a subgroup of hearts, atria were removed, and the total ventricles were used to determine the infarcted area as described previously [ 34 , 35 ]. Briefly, frozen ventricles were cut to 7–8 equal slices and placed into triphenyl-tetrazolium chloride solution (Sigma-Aldrich, Saint Louis, MO, USA) for 10 min at 37 °C followed by a 10 min formaldehyde fixation and phosphate buffer washing steps.…”
Section: Methodsmentioning
confidence: 99%
“…After glycosylation, the permeability, half-life, and analgesic activity of the BBB significantly improves . O-Linked glycosylation of the opioid peptide amide (Tyr- d -Thr-Gly-Phe-Leu-Ser-NH2) on Ser6 significantly increases BBB permeability (from 1.0 ± 0.2 μL min –1 ·g –1 to 2.2 ± 0.2 μL min –1 ·g –1 ), and enhances serum stability and the pain effect . Further study has found that different sugar-modified peptides lead to different tissue distributions.…”
Section: Peptide Modificationmentioning
confidence: 99%
“…200 O-Linked glycosylation of the opioid peptide amide (Tyr-D-Thr-Gly-Phe-Leu-Ser-NH2) on Ser6 significantly increases BBB permeability (from 1.0 ± 0.2 μL min −1 •g −1 to 2.2 ± 0.2 μL min −1 •g −1 ), and enhances serum stability and the pain effect. 201 Further study has found that different sugar-modified peptides lead to different tissue distributions. Although glycosylation reduces the fat solubility of peptides, it increases the amphiphilicity of peptides, which is very important in promoting the transportation of peptides across the BBB through adsorption-mediated cell transport.…”
Section: Peptide Modificationmentioning
confidence: 99%
“…, i.p. ) [ 40 , 41 , 42 , 43 , 44 , 45 ]. Our laboratory has extensively investigated glycosylation as a means to address the concerns of BBB permeability and stability for many endogenous peptides including opioid peptides, angiotensin 1 – 7 , and PACAP [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%